The Relevance of the Interpretation of The Qur’an with Qaul Al-Ṣaḥābah as a source of Islamic law in the current era - Maghfirah Maghfirah; Zulkifli Zulkifli (Institut Agama Islam Negeri (IAIN) Curup, 2022)
The interpretation of the Qur’an with Qaul al-ṣaḥābah is a product of classical scholars. Interpretation with Qaul al-ṣaḥābah is considered as a very representative explanation of the truth of the understanding of the Qur’an because they are still meeting with the Prophet Muḥammad so that there are not many deviations. But this method of interpretation is often forgotten in the writing of tafsīr. Therefore, the purpose of this study is to analyze the process of interpretation of the Qur’an conducted by ṣaḥābah. This article is a research library with a descriptive approach to collect documentation data from various articles, books then analyzed by content analysis. The results of this research are the strengths of Tafsīr al-Ṣaḥābah are that they are neutral regardless of political interests or schools of thought, are free from the history of isrā’iliyyāt, and no difference. While its weakness is not yet interpreted broadly and in detail, it is still partial and free of critical nature. In some instances in the current era, it is possible to make laws based on Qaul al-ṣaḥābah as one of the sources of Islamic law. The similarity of this research with previous research is to discuss the interpretation of Qaul al-Ṣhaḥābah, including the characteristics and instruments and examples of interpretations of the Qur’an carried out by Ṣaḥābah, such as Ibn’ Abbās, Ibn Masʻūd, ‘Āisyah, Abū Hurairah and ‘Alī bin Abī Ṭālib. While the difference is this research found the strengths and weaknesses of the interpretation of Qaul al-Ṣhaḥābah. In the discussion, this article also analyzes Qaul al-Ṣhaḥābah as a source of Islamic law in the current era